Genetic potential of segregating cowpea progenies regarding inflorescence type - Barros, Fábio Ribeiro; da Anunciação Filho, Clodoaldo José; Rocha, Maurisrael de Moura; Nunes, José Airton Rodrigues; Damasceno e Silva, Kaesel Jackson; Freire Filho, Francisco Rodrigues; Ribeiro, Valdenir Queiroz (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the genetic yield potential of segregating cowpea progenies regarding inflorescence type. Sixty‑eight F4 progenies obtained from the backcrosses (TV x 5058‑09C x Curly‑purple) x TV x 5058‑09C, and (AU94‑MOB‑816 x Curly‑purple) x AU94‑MOB‑816, with parents, were evaluated. Two experiments were carried out in a randomized complete block design with 17 progenies and four replicates, in a split‑plot arrangement regarding inflorescence: simple and composite. The statistical analysis was carried out by mixed models via REML/BLUP procedure. The estimates of genetic variance were significant for all evaluated traits. The traits peduncle length, average number of pods per peduncle, and initial flowering showed high variability and expression of the composite inflorescence genetic component. Progenies with simple inflorescence show similar genetic yield potential to the progenies with composite inflorescence. The progenies resulting from the backcrosses (AU94‑MOB‑816 x Curly‑purple) x AU94‑MOB‑816 are promising as a strategy to increase the current levels of grain yield in cowpea.